2015
DOI: 10.1007/s00204-015-1559-9
|View full text |Cite
|
Sign up to set email alerts
|

Activation of peroxisome proliferator-activated receptor α ameliorates perfluorododecanoic acid-induced production of reactive oxygen species in rat liver

Abstract: Perfluorododecanoic acid (PFDoA) is a ubiquitous environmental pollutant known to cause hepatocellular hypertrophy; however, the mechanisms of hepatotoxicity remain poorly understood. In this study, male rats were exposed to 0, 0.05, 0.2 and 0.5 mg/kg/day of PFDoA for 110 days. After two-dimensional differential gel electrophoresis and MALDI-TOF/TOF analysis, 73 differentially expressed proteins involved in lipid metabolism, inflammation, stress response and other functions were successfully identified. Among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 66 publications
3
10
0
Order By: Relevance
“…Kato et al (2015) have reported that hypertrophy, necrosis, and inflammatory cholestasis were observed in the liver after chronic administration of PFDoA at a dose of 0.5 and 2.5 mg/kg for 42-47 days in male rats. Hepatotoxicity of PFDoA has been shown to be due to production of reactive oxygen species in rats (Liu et al, 2016). Our present study showed high accumulation of PFDoA in the liver.…”
Section: Discussionsupporting
confidence: 62%
“…Kato et al (2015) have reported that hypertrophy, necrosis, and inflammatory cholestasis were observed in the liver after chronic administration of PFDoA at a dose of 0.5 and 2.5 mg/kg for 42-47 days in male rats. Hepatotoxicity of PFDoA has been shown to be due to production of reactive oxygen species in rats (Liu et al, 2016). Our present study showed high accumulation of PFDoA in the liver.…”
Section: Discussionsupporting
confidence: 62%
“…FAO-relevant genes [except enoyl - CoA hydratase 3 - hydroxyacyl CoA dehydrogenase (Ehhadh), carnitine O - acetyltransferase (Crat) and solute carrier family 25 member 20 (Slc25a20) ] were significantly reduced in mouse renal tissue following zoledronate treatment (Fig. 4 g) (Kang et al 2015 ; Li et al 2008 ; Polinati et al 2009 ; Liu et al 2016 ), pointing to defects in FAO in mouse kidney by zoledronate administration. Long-chain FAs are the main energy source for renal tubular epithelial cells (Kang et al 2015 ), which enter the cells mostly through several membrane proteins, including FA carrier CD36 and FA transport proteins (Verhulst et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…EPA and DHA also displayed an important effect on proteins of nitrogen metabolism. Among them, Cps1, which is a known target of carbonylation in the liver [ 30 ] and Ass1, which acts in the ammonia detoxification and whose expression is submitted to both hormonal and nutritional regulation. The carbonylation of liver Ass1 observed under HFHS diets could affect the optimal removal of toxic ammonia, and finally, would lead to metabolic disturbances as hyperammonemia [ 31 ].…”
Section: Discussionmentioning
confidence: 99%